What to do when you get dumped : a guide to unbreaking your heart - Hopkins, Suzy (Former newspaper reporter); Bateman, Hallie (Bloomsbury Publishing Inc., 2025)
"From the beloved mother-daughter team who brought us What to Do When I'm Gone, a poignant, funny, heartfelt, and gorgeously illustrated guide to navigating the pain and complexity of getting dumped. After Suzy Hopkins's husband of thirty years unexpectedly left her to pursue an old flame, her grief was so overwhelming that she thought her own heart might stop. How do you take the first step forward after losing such an integral part of your life? In What to Do When You Get Dumped, the mother-daughter duo of Hopkins and her New Yorker-illustrator extraordinaire daughter Hallie Bateman offer an incisive, tender, appealingly illustrated guide to "unbreaking" your heart. Using a countdown from the moment you're dumped, the book offers humor and hope as it guides readers on the journey to find new meaning and purpose in a life that's yours alone. Lighthearted, impactful, and deeply consoling, What to Do When You Get Dumped provides the wisdom to emerge from a breakup smarter, stronger, and with the unshakable knowledge that you are worthy of lasting love."--Amazon.com.